2015
DOI: 10.1093/annonc/mdv290
|View full text |Cite
|
Sign up to set email alerts
|

BRAF codons 594 and 596 mutations identify a new molecular subtype of metastatic colorectal cancer at favorable prognosis

Abstract: BRAF codon 594 or 596 mutated mCRCs are different from BRAF V600E ones in terms of molecular features, pathological characteristics and clinical outcome. This is consistent with preclinical evidences of a kinase inactivating effect of these mutations. The role of CRAF in transducing the intracellular signal downstream BRAF 594 or 596 mutated proteins opens the way to further preclinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
109
5
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 22 publications
25
109
5
3
Order By: Relevance
“…The frequency of BRAF D594G mutations in colorectal cancers has been reported as 0.3-2.3% of colorectal cancers [13,14,15,16,17,18,19,20,21]. To date, 22 colorectal cancers with BRAF D594G mutations have been registered in the COSMIC database (http://cancer.sanger.ac.uk/cosmic); however, since BRAF D594G mutations are rare in colorectal cancer, it is difficult to draw conclusions based on these data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of BRAF D594G mutations in colorectal cancers has been reported as 0.3-2.3% of colorectal cancers [13,14,15,16,17,18,19,20,21]. To date, 22 colorectal cancers with BRAF D594G mutations have been registered in the COSMIC database (http://cancer.sanger.ac.uk/cosmic); however, since BRAF D594G mutations are rare in colorectal cancer, it is difficult to draw conclusions based on these data.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that colorectal cancers with rare BRAF mutations, including in codons 594 and 596, were MSS in MSI status and showed favorable prognoses compared to those with BRAF V600E mutations [21]. Moreover, the kinase activity of BRAF mutations at codon 594 was reported to be low [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Dagegen waren die BRAF-594-und 596-Mutationen häu-figer mit rektalen und nicht-muzinösen Tumoren ohne peritoneale Metastasierung assoziiert. Die untersuchten BRAF-594-und 596-Tumoren waren alle Mikrosatelliten-stabil und waren darüber hinaus mit erheblich längeren Überlebenszeiten (Median 62,0 vs. 12,6 Monate; HR 0,36, p = 0,002) verbunden [1060].…”
Section: Braf-mutationunclassified
“…Quellen: [1060,1117] Konsens Hintergrund Eine BRAF-V600-Mutation wird bei 8 -12 % der mKRK-Patienten beobachtet. Häufiger sind Frauen betroffen, das Erkankungsalter ist meist höher.…”
Section: Level Of Evidenceunclassified
“…The coexistence of both KRAS and BRAF is uncommon in CRC patients. In the present study, patients ID 3 and 19 carried 2 different BRAF mutations: Val600Glu (A>T, rs113488022) [54] and Gly596Val (C>A), both variants are pathogenic with different molecular, pathological characteristics and clinical outcomes [55]. These two patients could be benefit from anti-BRAF in combination with anti-EGFR or anti-MAPK [56].…”
Section: Tp53 Showed the Highest Percentage Of Germline Inherited Mutmentioning
confidence: 85%